Cognitive computing and big data analytics - Hurwitz, Judith; Kaufman, Marcia; Bowles, Adrian, 1952- (John Wiley & Sons, 2015)
This book provides detailed guidance toward building a new class of systems that learn from experience and derive insights to unlock the value of big data. It helps technologists understand cognitive computing's underlying technologies, from knowledge representation techniques and natural language processing algorithms to dynamic learning approaches based on accumulated evidence, rather than reprogramming. Case examples from financial, healthcare, and manufacturing walk readers through the design and testing of cognitive systems. Topics include: how cognitive computing evolved from promise to reality; elements of a cognitive computing system; hardware and software technologies behind cognitive computing; evaluation of your own application portfolio; cognitive computing capabilities to transform the organization. --